Cryptosporidiosis in children less than three years old in Ciliwung Riverside, Kampung Melayu Village, Jakarta, Indonesia - Herbowo A. Soetomenggolo; Agus Firmansyah; Agnes Kurniawan; Partini P. Trihono (Paediatrica Indonesiana, 2008)
Background Cryptosporidium infection is often found in children,especially children below three years old. Many risk factors canaffect cryptosporidiosis prevalence. At this moment, the prevalenceand risk factors of cryptosporidiosis in children in Jakarta areunknown.Objectives To determine the cryptosporidiosis prevalence, clinicalmanifestations, and risk factors in children below three years old.Methods This cross sectional study involved 474 subjects betweenthe age of 0 to 35 months in Ciliwung riverside, Kampung Melayuvillage, from December 2005 until April 2006. Stool specimenswere examined using modified acid-fast staining. Nutritional statuswas measured based on actual body weight over ideal body weightratio (NCHS-CDC 2000).Results Cryptosporidium cysts were found in stool sample of 10/474 subject (2.1%). Most of the cases used ground water as asource for drinking and washing. All positive cases lived in houseswith bad sanitation, flooded house and 9/10 cases had a crowdedhousehold. Cat and mice were the two most frequently foundanimals around the house. We found five asymptomatic cases andall of the cases were undernourished.Conclusions The prevalence of cryptosporidiosis in this study is2.1%. Due to small number of cases no risk factor could beidentified. Use of groundwater as a water source, bad sanitation,cat and mice around the house, flooded house, crowded householdand undernourishment might be related to cryptosporidiosisprevalence. Half of the infected children were asymptomatic.